Comparative analysis of ERP‑enabled maintenance management at thermal and nuclear power plants in Ukraine and world‑wide - Markov, A. V.; Kavercev, V. L. (National Technical University "Kharkiv Polytechnic Institute", 2025)
The paper benchmarks Enterprise Resource Planning (ERP) applications for planned and emergency maintenance at power‑generation facilities. Drawing on 2020-2025 case studies and open‑source performance data, it identifies best practices that typically cut unplanned downtime by 10-15% and maintenance OPEX by up to 15%.
Keywords: ERP; maintenance; CMMS; predictive analytics; OPEX; costbenefit; power generation; Ukraine